Analysis of the Class 5 Hadith Curriculum at Madrasah Ibtidaiyah Fitrah Insani Garut - Muhammad Hasbullah; Mulyawan Safwandy Nugraha; Ujang Dedih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to analyze the hadith curriculum on the material of the virtues of sharing and charity which is discussed in grade 5 Madrasah Ibtidaiyah Fitrah Insani Garut, including material objectives, scope, graduate competencies, approaches, strategies, and learning methods. The research method used in this research is a case study using a qualitative approach, this research was conducted at a place or institution about a certain discussion, namely the analysis of the hadith curriculum in grade 5 Madrasah Ibtidaiyah Fitrah Insani. The results showed that the analysis of the hadith curriculum in Madrasah Ibtidaiyah Fitrah Insani Garut involved planning and implementing learning to achieve learning objectives, namely, developing the ability of students in reading and writing Hadith, introducing Hadith as a guide in everyday life other than the Qur'an, practicing Hadith with behavior in everyday life. Hadith curriculum analysis is inseparable from the development of curriculum foundations, namely philosophical-theological foundations, sociocultural foundations, psychological foundations, and the foundation for the development of science and technology. These four foundations have an important role as the basis of learning components such as formulating goals for students, achieving both mastered knowledge and attitudes, adjusting the needs of students so that they can choose and use the right approaches, strategies, and methods